The Weapondollar-Petrodollar Coalition - Jonathan Nitzan; Shimshon Bichler (The Global Political Economy of Israel, 2002)
A theoretical and historical account of the global political economy of oil, armament and capital accumulation in the Middel East.
Keywords: 330; arms; accumulation; capital; capitalism; centralization; competition; conflict; corporation; crisis; development; distribution; dual economy; elite; energy; finance; globalization; growth; imperialism; distribution; institutionalism; IPE; Israel; Middle East; military; national interest; security; oil; OPEC; ownership; peace; politics; power; privatization; profit; ruling class; sabotage; stagflation; state; stock market; technology; TNC; United States; US; violence; war; Zionism